1989
DOI: 10.2331/suisan.55.559
|View full text |Cite
|
Sign up to set email alerts
|

Changes in content of ATP-related compounds, homarine, and trigonelline in marine invertebrates during ice storage.

Abstract: Marine invertebrates consisting of 9 species of mollusks, 7 of crustaceans and 3 of echinoderms, were analyzed for ATP-related compounds, homarine, and trigonelline during ice storage. The determination was carried out by a newly improved HPLC system which made it possible to separate and micro-quantify the 9 authentic ATP-related compounds. The results showed that besides adenine nucleotides, IMP was detected at the range of 0.1 to 5.5 ƒÊmol/g in the muscles of all species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 1 publication
3
18
0
Order By: Relevance
“…The high levels of A.E.C. and ATP in the muscle of the oyster, hard clam, and ark-shell obtained in this investigation indicated that specimens used in this study were in a better condition before the experiment than those in the report by Suwetja et al 10) In fact, in the preliminary experiment, we confirmed that the A.E.C. value at time 0 decreased when the speci mens were exposed to air for few days.…”
Section: Discussionsupporting
confidence: 41%
“…The high levels of A.E.C. and ATP in the muscle of the oyster, hard clam, and ark-shell obtained in this investigation indicated that specimens used in this study were in a better condition before the experiment than those in the report by Suwetja et al 10) In fact, in the preliminary experiment, we confirmed that the A.E.C. value at time 0 decreased when the speci mens were exposed to air for few days.…”
Section: Discussionsupporting
confidence: 41%
“…The muscle of several species of bivalves was analyzed and it was reported that with no or less activity of AMP deaminase, IMP did not accumulate during storage at -5℃ and that ATP degradation proceeded as follows: ATP → ADP → AMP → AdR → HxR → Hx in surf clam Spisula sachalinensis and scallop Pecten yessoensis and P. albicans or ATP → ADP → AMP → AdR → Ad in ark shell Anodara broughtonii and abalone Haliotis discus (Saito, 1961;Arai, 1961b;Iwamoto et al, 1970). However, different reports are available on the accumulation of IMP in postmortem molluscan muscles (Suwetja et al, 1989;Sagedhal et al, 1997). It was detected that there was a large amount of IMP in edible parts of the short-neck clam Tapes japonica (Konosu et al, 1965).…”
Section: Changes In Contents Of Atp-related Compounds Of Oyster Tissumentioning
confidence: 87%
“…It was detected that there was a large amount of IMP in edible parts of the short-neck clam Tapes japonica (Konosu et al, 1965). There are other reports that IMP, HxR and Hx were detected during storage in the muscle of the scallop Placopecten magellanicus (Hiltz and Dyer, 1970), oyster Crassostrea gigas (Suwetja et al, 1989;Sakaguchi et al, 1990), ark shell Anodara broughtonii, clam Meretrix lusoria and short-neck clam Tapes japonica (Sakaguchi et al, 1990). The results suggested the pathway: ATP → ADP → AMP → IMP → HxR.…”
Section: Changes In Contents Of Atp-related Compounds Of Oyster Tissumentioning
confidence: 90%
See 1 more Smart Citation
“…In marine shellfish, postmortem changes in the concentrations of ATP-related compounds (ARCs) have been investigated in detail to determine indices of freshness during storage [14][15][16][17][18][19][20][21]. Marine shellfish show seasonal changes in ARCs and free amino acids [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%